(untitled) (Journal of the College of Basic Education, 2023)
Derivatives represent financial contracts related to items outside the budget and determine their valueBased on indicators or related tools. Therefore, the process of managing and controlling itIts returns and the resulting risks are among the basic tasks of the owner or the one who makes the financial decision(Bank; financial institution) This research came to try to answer how to control theThe returns of these derivatives and that this task has been addressed through three chapters and conclusionsAnd recommendations:The first chapter deals with derivatives, their concept, types and management.The second chapter deals with risk, its concept and types.The third chapter - risk and return. Dealing with derivatives and managing them and achieving the required financial gain is done according to experienceAnd the efficiency of the decision-maker, so the process of qualifying this person and providing a database for him came inIntroduction to the things he needs to make the right decision.